A point-like enhanced resolution of experimental Aeolian tone using an iterative point-time-reversal-sponge-layer damping technique. (April 2021) - Mimani, A.
Highlights: Iterative time-reversal super-resolution algorithms are presented for Aeolian tone dipole. Multi-stage PTRSL iteration produced a point-like resolution by focusing acoustic power at the source location. Mesh-refinement significantly improved the results, especially at higher-stages. A sensitivity analysis investigated the effect of offset of PTRSL center on resolution and strength. PTRSL center-based iteration delivered enhanced source maps without knowledge of the predicted location. Abstract: This paper presents a time-reversal (TR) super-resolution algorithm which produces a point-like enhanced focal-resolution of experimental Aeolian tone source using iterative implementations of the Point-Time-Reversal-Sponge-Layer (PTRSL) which is based on focusing of acoustic power at the center of the damping domain. Two iteration methods were considered - the first one termed the Multi-stage PTRSL iteration, was based on a repeated implementation of the PTRSL damping centered at the predicted source location. Multi-stage PTRSL was shown to exponentially reduce the size of lift-dipole focal spots and their interfocal distance until an asymptotic limit is reached for a given mesh as the number of stages increase. Refining the mesh decreased the asymptotic limit signifying a better resolution, and for the finest mesh considered, the asymptotic transverse and longitudinal focal-resolution was given by λ / 30 and λ / 50, respectively, indicating a highly enhanced point-like resolution which is comparable to the result produced by an active sink. The second method, termed the PTRSL center-based iteration is based on carrying out a sensitivity analysis – it investigates the effect of deviation or offset of the center from the predicted location on the resolution and strength of Aeolian tone source. The sensitivity analysis revealed that although the First-stage PTRSL was effective when the offset was within a quarter-wavelength distance along a direction perpendicular to dipole-axis, the maximum resolution enhancement and increase in the Sound Pressure Level at focal points were obtained when the center and predicted location were co-incident. On the other hand, no tangible difference was observed between the First-stage map and that computed without PTRSL when the offset distance was substantially greater than half-wavelength, and away from the dipole-axis. Furthermore, a spatial root-mean-square average of the First- and Higher-stage sensitivity analysis maps was computed which produced the same predicted location and a significant resolution enhancement, thereby resolving ambiguity in source location. On the basis of these results, guidelines are formulated which enable the PTRSL center-based iteration technique to reconstruct enhanced source maps of the Aeolian tone without a-priori knowledge of the predicted location.